Awareness on the role of UiTM Zakat, Sedekah dan Wakaf centre (ZAWAF) among UiTM students / Mohamad Haziq Mohamad Rosli - Mohamad Rosli, Mohamad Haziq (2021)
The institution of zakat is one of the important institutions in Malaysia as well as in Islam itself. Awareness of the Role of UiTM Zakat, Sedekah and Wakaf Center (ZAWAF) among UiTM Students is the topic chosen in the researcher's study. There are a handful of students who have an awareness and understanding of this ZAWAF. However, to what extent of understanding and awareness do they have? How many students are aware of ZAWAF? There are still many students who do not know the role of ZAWAF in UiTM itself. Therefore, I am responsible for completing my research assignment by looking at the level of awareness of UiTM students on the topic of my research. The objectives and problems in my study can be achieved by distributing survey forms to 95 respondents using social media. In this project, I found that all parties need to play their respective roles so that the understanding and knowledge of the existence of ZAWAF and its role is very important in UiTM and also to the students themselves. Not only to UiTM students, but to all UiTM residents. In conclusion, this study to some extent gives awareness to the next generation to deepen the role of ZAWAF which is very important in UiTM and also to UiTM citizens themselves.